Earnings and Balance Sheet Conservatism in Malaysia - Marzuki, M.; Abdul Wahab, Effiezal Aswadi (Asian Academy of Manaagement and Penerbit Universiti Sains Malaysia, 2016)
The objective of this paper is to examine the impact of International Financial Reporting Standards (IFRS) on both earnings and balance sheet conservatism in Malaysia. Earnings conservatism has been used extensively in common-law countries such as the United States (US) and the United Kingdom (UK), which are known to have good financial reporting quality. In contrast balance sheet conservatism is more evident in code-law countries such as Japan and France, where accounting practice is highly influenced by the institutional culture similar to Malaysia such as political connection and family-firms. Since Malaysia uses international accounting standards adopted from common-law countries, we hypothesise that earnings conservatism will increase whereas balance sheet conservatism will decrease after the incorporation of IFRS in the financial reporting environment. Consistent with the hypothesis, we find that earnings conservatism and balance sheet conservatism increase and decrease respectively after Malaysia's convergence to IFRS. The results indicate that Malaysia has successfully adopted IFRS from common-law countries as earning conservatism increase after IFRS convergence.